Authentic Virtual World Education Facilitating Cultural Engagement and Creativity (Springer Singapore, 2018)
The book presents the possibilities and realities of virtual worlds in education through the application of 3D virtual worlds to support authentic learning, creativity, learner engagement and cultural diversity in higher education. It includes a unique variety of cross disciplinary approaches to research, teaching and learning in a virtual world, including analysis of data from the experiences of students in education, law, Chinese language, sustainability, computer architecture, business, health and the Arts. The book provides unique learning experiences that have celebrated the rich media of virtual world environments through the utilisation of affordances such as simulation, bots, synchronous interaction, machinima and games. The perspectives come from Australia and New Zealand higher education academics but transferable to any higher educational institution in the sector, worldwide, and is significant to various disciplines in the higher education field.